2011
DOI: 10.1007/s13204-011-0036-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manganese doping on the photoluminescence characteristics of chemically synthesized zinc sulfide nanoparticles

Abstract: The studies on luminescent II-VI semiconducting nanomaterials have attracted widespread attention recently, due to their potential applications in optoelectronic and biophotonic devices. Amongst other II-VI semiconductor nanoparticles (NPs), Mn 2? -doped ZnS NPs having large exciton binding energy and wide direct band gap at room temperature have drawn considerable attention for exploring its interesting optical properties. However, in this report, water-soluble Mn 2? -doped ZnS (ZnS:Mn) NPs with Mn 2? concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…If the size of the prepared nanoparticles is greater than the value of Bohr exciton radius of bulk SnO 2 , 2.7 nm [16], samples have a weak confinement and shift of absorption band gap due to quantum size effect is very small. Under such confinement the average particle size of the prepared nanoparticles is calculated from the blue shift of band gap energy through a simple relation derived in the effective mass model [23][24][25],…”
Section: Resultsmentioning
confidence: 99%
“…If the size of the prepared nanoparticles is greater than the value of Bohr exciton radius of bulk SnO 2 , 2.7 nm [16], samples have a weak confinement and shift of absorption band gap due to quantum size effect is very small. Under such confinement the average particle size of the prepared nanoparticles is calculated from the blue shift of band gap energy through a simple relation derived in the effective mass model [23][24][25],…”
Section: Resultsmentioning
confidence: 99%
“…Kole and co-workers have reported that the increase in particle size and decrease in density of surface states leads to a red shi in emission wavelength. 30 In addition to this, Karar et al 28 have mentioned that the red shi with Mn ion concentration can be attributed to a change in band gap structure of ZnS upon Mn 2+ ion incorporation or Mn-Mn ion interactions. All these points suggest that the Mn ions are getting well incorporated into the host ZnS lattice and shiing the emission to a longer wavelength with increasing doping concentration.…”
Section: Structure and Microstructure Analysismentioning
confidence: 94%
“…The intensity of the two bands (at 451 and 469 nm for MnS/ZnS@Mt) was also increased together with the increase of the band due to MnS and ZnS, indicating the increase of the photoluminescence intensity of the product. The yellow emission shoulder at around 550 nm was clearly seen in the PL spectra of MnS/ZnS@Mt and MnS/CdS@ Mt, supporting the incorporation of Mn 2 + ions in the lattice site of ZnS or CdS (Hu and Zhang, 2006;Kole and Kumbhakar, 2011). The photoluminescence intensities of the products increased in the followed sequence of ZnS/CdS@Mt b MnS/CdS@Mt b MnS/ZnS@Mt, indicating the quantum confinement effect.…”
Section: Resultsmentioning
confidence: 68%